Modeling of the ions rejection of sugar beet press water by nanofiltration using the “DSPM” model - M. Shahidi Noghabi; S.M. Mousavi; S.M.A. Razavi; M. Elahi (Pizhūhish va Nuāvarī dar ̒Ulūm va Sanāyi̒-i Ghaz̠āyī, 2013)
In this study, the beet pulp pressing water using nanofiltration process investigated. The effect of temperature (25, 40 and 55 °C), the transmembrane pressure (10, 15 and 20 bar) and the brix (1, 2, and 30) on the rejection of sodium, potassium, calcium, magnesium, chloride and sulfate was studied. Then, physical modeling of sugar beet press water nanofiltration was performed by DSPM and compared with experimental data. The computer program of this model was written by MATLAB software (version 2008). In this modeling, ions rejection predicted based on ions properties (such as initial concentration, charge, coefficient diffusion and hydrodynamic radius), solution properties (such as viscosity and temperature), operating condition (TMP) and membrane properties (such as charge density, pore size and thickness of dense layer). The results showed that DSPM can highly predict the ions rejection under different operating conditions of sugar press water nanofiltration (R=0.970).